Artificial Intelligence and Heath Psychology: Applications, Ethical Challenges, and Future Directions - Habiba KHABIRI; Aicha ZIANI (International Journal of Scientific Research and Innovative Studies, 2026)
Artificial Intelligence (AI) has increasingly been integrated into various healthcare services, including mental health and psychological care. This narrative review explores the applications, psychological impacts, and ethical considerations of AI technologies in the field of Health Psychology a branch of psychology concerned with the interplay between psychological processes and health outcomes. Drawing on systematic reviews and empirical studies published between 2015 and 2025, the article examines how AI is used for digital interventions, early detection, behavioral monitoring, and personalized psychological support. It also critically discusses ethical challenges such as data privacy, algorithmic bias, transparency, and the risk of undermining the therapeutic relationship. The review concludes with recommendations for responsible implementation and future research directions that center on maintaining humanistic values in psychological practice. Keywords: Artificial Intelligence; Health Psychology; Digital Mental Health; Ethical Issues; Psychological Interventions; Behavioral Health Received Date: December 20, 2025 Accepted Date: January 12, 2026 Published Date: February 01, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/565